A new 2.4 GPa extra-high strength steel with good ductility and high toughness designed by synergistic strengthening of nano-particles and high-density dislocations. (15th March 2020) - Liu, Tianqi; Cao, Zhaoxi; Wang, Hui; Wu, Guilin; Jin, Jianjun; Cao, Wenquan
Abstract: A new 0.25C2Cr10Ni8Co2Mo2Al steel was designed and fabricated by vacuum induction melting, forging and heat treatments. Excellent mechanical properties with a combination of a 2.4 GPa ultimate tensile strength, a 2.1 GPa yield strength, a 11.4% total elongation and a 37 J/cm 2 V-notch impact toughness were obtained. Such a combination of strength–ductility–toughness of the present steel is much superior than any reported conventional ultrahigh strength steel. The excellent mechanical properties of the steel can be well interpreted by synergistic strengthening of high-density dislocations, strong segregations of C, Mo and Cr on dislocations and massive nanosized NiAl precipitations. Graphical abstract: An extra-high strength steel of 0.25C2Cr10Ni8Co2Mo2Al was designed and the combined properties could be well interpreted by the microstructure featured with high dense precipitation of NiAl particle, high dense dislocations and the co-segregation of Cr, Mo and Co. Image, graphical abstract